Sistema de iluminación para la cancha sintética y parque recreativo doce de octubre del municipio Los Patios, Norte de Santander (2021)
The integral degree work consists of carrying out a lighting system design for the synthetic court and Doce de Octubre recreational park in the municipality of Los Patios Norte de Santander, for which the methodological projection was carried out step by step in the design of a lighting system with LED technology, based on a detailed analysis regarding energy consumption, already that LED technology allows to reduce long-term energy consumption, obtaining economic benefits for the Mayor of Los Patios. During the development of this project, the standards of electrical installations and public lighting of Los Patios were taken into account through the responsible entities such as RETIE and RETILAP, for the approval of the project and leave the community in operation. The design is carried out by means of the calculations obtained from the reflectors that were used for the project; Once the calculations have been obtained, the design is carried out in the DIALUX 4.12 software, which shows in detail the projections, photometric calculations of the lighting system.